A study on the challenges and importance of vehicular network in the context of Bangladesh - Naz, Farah; Chowdhury, Tanzina Akter; Sabah, Sanjida Hossain; Ferdous, Hasan Shahid (© 2011 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 2011 IEEE Student Conference on Research and Development, SCOReD 2011; Cyberjaya; Malaysia; 19 December 2011 through 20 December 2011 [© 2011 IEEE ] The conference paper's definite version is available at: http://doi.org/10.1109/SCOReD.2011.6148748